Menggali Nilai-Nilai Pengelolaan Lingkungan Hidup Berbasis Kearifan Lokal Lio Sebagai Bentuk Pengintegrasian Dengan Pendidikan Pancasila (Studi Kasus di Desa Koro Bhera Kecamatan Mego Kabupaten Sikka) - Redemtus Frento Poto; H. Rodja Abdul Natsir; Moh. Fitri (CV. Rumoh Aceh Publishing, 2026)
This study aims to determine the extent to which the values ​​of environmental management based on local wisdom are explored as a form of integration with Pancasila education and what are the inhibiting factors in the development of the environmental management sector. This research method was carried out with a qualitative descriptive approach. The data sources used are primary data sources and secondary data sources. The informants involved in this study were in Koro Bhera Village. Mega District. Kab. Sikka. Data collection techniques used are observation techniques, interviews and documentation. Data analysis techniques include data reduction, data display, and verification. The results of the research show that Digging the Values ​​of environmental management based on local wisdom as a facilitator, motivator and dynamicator. The tasks carried out by the local community and the village government can be said to be quite effective and maximal enough in carrying out their duties by providing motivation, training and continuing to make improvements which will later bring about changes in Environmental Management.